Region-Wide Annual Glacier Surface Mass Balance for the European Alps From 2000 to 2016 - Davaze, Lucas; Rabatel, Antoine; Dufour, Ambroise; Hugonnet, Romain; Arnaud, Yves (Frontiers in Earth Science, 2020)
Studying glacier mass changes at regional scale provides critical insights into the impact of climate change on glacierized regions, but is impractical using in situ estimates alone due to logistical and human constraints. We present annual mass-balance time series for 239 glaciers in the European Alps, using optical satellite images for the period 2000-2016. Our approach, called the SLA-method, is based on the estimation of the glacier snowline altitude (SLA) for each year combined with the geodetic mass balance over the study period to derive the annual mass balance. In situ annual mass-balances from 23 glaciers were used to validate our approach and underline its robustness to generate annual mass-balance time series. Such temporally resolved observations provide a unique potential to investigate the behavior of glaciers in regions where few or no data are available. At the European Alps scale, our geodetic estimate was performed for 361 glaciers (75% of the glacierized area) and indicates a mean annual mass loss of -0.74±0.20 m w.e. yr-1 from 2000 to 2016. The spatial variability in the average glacier mass loss is significantly correlated to three morpho-topographic variables (mean glacier slope, median and maximum altitudes) altogether explaining 36% of the observed variance. Comparing the mass losses from in situ and SLA-method estimates and taking into account the glacier slope and maximum elevation, we show that steeper glaciers and glaciers with higher maximum elevation experienced less mass loss. Because steeper glaciers (>20°) are poorly represented by in situ estimates, we suggest that region-wide extrapolation of field measurements could be improved by including a morpho-topographic dependency. The analysis of the annual mass changes with regard to a global atmospheric dataset (ERA5) showed that: i) extreme climate events are registered by all glaciers across the European Alps and we identified opposite weather regimes favorable or detrimental to the mass change; ii) the interannual variability of glacier mass balances in the “central European Alps” is lower; and iii) current strong imbalance of glaciers in the European Alps is likely mainly the consequence of the multi-decadal increasing trend in atmospheric temperature, clearly documented from ERA5 data.